2010
DOI: 10.1371/journal.pmed.1000332
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity Attenuates the Genetic Predisposition to Obesity in 20,000 Men and Women from EPIC-Norfolk Prospective Population Study

Abstract: Shengxu Li and colleagues use data from a large prospective observational cohort to examine the extent to which a genetic predisposition toward obesity may be modified by living a physically active lifestyle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
249
3
8

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 261 publications
(289 citation statements)
references
References 33 publications
26
249
3
8
Order By: Relevance
“…The prospective Norfolk study of 20 000 men and women showed physical activity to attenuate the genetic predisposition to common obesity by 40%, as estimated by the number of risk alleles carried for 12 recently identified obesity predisposing loci. 34 In the same study, the genetic risk score was positively associated with weight gain in inactive subjects, but negatively associated in physically active subjects. Similar findings in a twin study of the United States, Finnish and Danish twins lend support to the notion that physical exercise can indeed counteract the genetic predisposition to obesity; estimates of the heritability of waist circumference, percentage of body fat and BMI significantly declined in those individuals classified as having 'high' physical activity.…”
Section: Development Of Obesitymentioning
confidence: 87%
“…The prospective Norfolk study of 20 000 men and women showed physical activity to attenuate the genetic predisposition to common obesity by 40%, as estimated by the number of risk alleles carried for 12 recently identified obesity predisposing loci. 34 In the same study, the genetic risk score was positively associated with weight gain in inactive subjects, but negatively associated in physically active subjects. Similar findings in a twin study of the United States, Finnish and Danish twins lend support to the notion that physical exercise can indeed counteract the genetic predisposition to obesity; estimates of the heritability of waist circumference, percentage of body fat and BMI significantly declined in those individuals classified as having 'high' physical activity.…”
Section: Development Of Obesitymentioning
confidence: 87%
“…It can also reduce obesity risk especially in those with a high genetic susceptibility (108) . Indeed, the most recent study of gene-lifestyle interactions has shown that the adverse influence of sedentary behaviour (TV watching) and beneficial influence of increasing leisure-time physical activity appear to have separate influences on the genotypic propensity for obesity (109) .…”
Section: Discussionmentioning
confidence: 99%
“…The advantages of physical activity were shown in a recent study, where none of the dietary approaches alone predicted weight change; however, in combination with frequent exercise, limiting portion sizes proved to be the most successful strategy for weight gain prevention. 41 Li et al 42 have shown that an obesity gene risk score, based on 12 obesity-related genes, is associated with prospectively assessed weight change, the direction of which is dependent on physical activity levels. Among sedentary subjects, risk alleles are associated with weight gain, but among physical activity subjects, the same risk alleles predict weight loss.…”
Section: Does Dieting Make You Fatmentioning
confidence: 99%